Nutrients and soil surface management on highland vertisols of Ethiopia - Haque, I.; Mamo, T.; Astatke, A. (International Livestock Centre for Africa, 1992)
Summarises available information on bulk density and porosity, soil moisture infiltration, N, P and mineralogy. Literature on the phosphorus (P) status of soils, P nutrition of forage legumes and crops, mycorrhizal and P nutrition, species and varietal variation in response to P, P sorption isotherms and P fertilization based on forage based cropping systems is reviewed. The review also highlights the response of various crops to N in the presence of appropriate rhizobium, microbial studies and biological nitrogen fixation and its cycling in vertisol cropping. A short discussion on soil surface management for erosion control and sustained productivity is presented. Soil moisture dynamics and supplementary irrigation for double cropping is also proposed.